Performance Enhancement of Vapor Compression Refrigeration System using CuO Nano Particles in CARE 30 Test Rig - M. Kaleemullah; H. Zahir; M. Azizuddin (Iranica Journal of Energy and Environment, 2020)
The refrigeration system excution with the nano oil was explored to enhance the coefficient of performance (COP) of the vapor compression refrigeration system (VCRS) using CARE 30 which is a mixture of 50% refrigerant R200 and 50% refrigerant R600a in which 1 gram of Copper oxide (CuO) nano particles (NP) are used.  Nano lubricant was used in the compressor of R-134a refrigeration system (compatible with CARE 30) mixed with polyolester (POE) oil.  To execute this examination, a test setup was planned and fabricated in the workshop.  The outcome demonstrates that CARE 30 and POE oil with CuO NP works typically and securely in the refrigeration system.  The refrigeration system performance found is better than the customary CARE 30 and POE oil only refrigertion system.  Therefore, the nano lubricant (POE compressor lubricant mixed with CuO NP) could be used as a vital piece of refrigeration system to lower the energy consumption and for the enhancement of COP of VCRS.